Patterns of Legume Purchases and Consumption in the United States - Semba, Richard D.; Rahman, Nihaal; Du, Shutong; Ramsing, Rebecca; Sullivan, Valerie; Nussbaumer, Elizabeth; Love, David; Bloem, Martin W. (Frontiers in Nutrition, 2021)
Background: Legumes are an inexpensive, healthy source of protein, fiber, and micronutrients, have low greenhouse gas and water footprints, and enrich soil through nitrogen fixation. Although higher legume consumption is recommended under US dietary guidelines, legumes currently comprise only a minor part of the US diet. Objectives: To characterize the types of legumes most commonly purchased by US consumers and patterns of legume purchases by state and region, seasonality of legume purchases, and to characterize adults that have a higher intake of legumes. Methods: We examined grocery market, chain supermarket, big box and club stores, Walmart, military commissary, and dollar store retail scanner data from Nielsen collected 2017-2019 and dietary intake from the National Health and Nutrition Examination Survey (NHANES), 2017-2018. Results: The five leading types of legumes purchased in the US were pinto bean, black bean, kidney bean, lima bean, and chickpea. The mean annual per capita expenditure on legumes based on grocery purchases was 4.76 during 2017-2019. The annual per capita expenditure on legumes varied greatly by state with highest expenditure in Louisiana, South Carolina, Florida, Alabama, Mississippi, and lowest expenditure in Washington, New York, and Wisconsin. There were large regional differences in the most commonly purchased legumes. Of 4,741 adults who participated in the 24-hour dietary recall in NHANES, 2017-2018, 20.5% reported eating any legumes in the previous 24 hours. Those who consumed legumes were more likely to be Hispanic, with a higher education level, with a larger household size (all P<0.05), but were not different by age, gender, or income level compared to those who did not consume legumes. Conclusions: Although legumes are inexpensive, healthy, and a sustainable source of protein, per capita legume intake remains low in the US and below US dietary guidelines. Further insight is needed into barriers to legume consumption in the US.